CORONAVIRUS DISEASE - 19 – A SERIOUS THREAT TO PUBLIC HEALTH - SAPKOTA, NIRAJ KHATRI; KOIRALA, ARUN; YADAV, RAM LOCHAN; TIMILSINA, SAMEER; BHUSAL, PUJAN (Innovare Journal of Sciences, 2020)
The year 2020 is a public health emergency period declared globally by the WHO when on March 11, 2020, the deadly novel coronavirus-2019 causing severe acute respiratory syndrome (SARS) extended its stride in almost 150 countries commenced from Wuhan wet market, China led to declare globally as pandemic disease. Till date, more than 3 million are worldwide infected and the number is still in progression and nearly 200,000 people have succumbed, nearly 50,000 people only in United State died of this virus. Hence, this virus has brought global disaster. Therefore, this review is attempting to present a picture on coronavirus disease (COVID)-19 in terms of epidemiology, pathophysiology, and diagnosis, treatment, on the basis of available literature after search from the renowned database, especially focusing on public health impact. Treatment strategy is most essential part to focus for public health management and to save more life from this pandemic. As of date, there are no specific drugs for its treatment only repurpose drugs are employed for the hospitalized patient in present scenario, for example, Remdesivir made for Ebola is being use now in Covid-19 which inhibit replicase enzyme and reduced viral load, chloroquine and hydroxychloroquine an antimalarial drugs which prevent binding of S1 domain of Spike protein of SARS coronavirus 2 with Angiotensin Converting Enzyme-2 receptor and prevent fusion by S2 subunit thus overall prevent entering into the human susceptible cells along with it increases endosomal unstability by increasing pH. In addition, supportive care management such as supplemental oxygen and mechanical ventilation procedure is highly supportive to the critical patient. There infected more than 10 million people with more than 0.5 million death, the observation of July 7, 2020.